Kajian Empiris Model Gravitasi Faktor Penentu Ekspor Indonesia ke Negara Anggota Organisasi Kerjasama Islam (OKI) - Ardila Prihadyatama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
This study identifies the impact of economic factors on bilateral exports between Indonesia and OIC member countries. Estimation panel data for the graphical model, the data covers the period 1997 to 2021. The gravity estimate implies the importance of size effects, economic emergence rates, inflation rates, and exchange rates as determinants of Indonesia's exports to OIC countries. The individual effect estimates show how far the distance and institutions are in increasing exports of Indonesia and OIC member countries.